2012
DOI: 10.1158/0008-5472.can-11-3513
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of PI3K from ErbB3 Impairs Mammary Gland Development but Does Not Impact on ErbB2-Induced Mammary Tumorigenesis

Abstract: The formation of ErbB2/ErbB3 heterodimers plays a critical role in ErbB2-mediated signaling in both normal mammary development and mammary tumor progression. Through 7 phosphoinositide 3-kinase (PI3K) phosphotyrosine-binding sites, ErbB3 is able to recruit PI3K and initiate the PI3K/AKT signaling pathway. To directly explore the importance of the ErbB3/PI3K pathway in mammary development and tumorigenesis, we generated a mouse model that carries a mutant ErbB3 allele lacking the seven known PI3K-binding sites … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…Moreover, increased Ras activation could also contribute to PI3K signaling. In a similar study, Erbb3-mediated PI3K signaling was shown to be dispensable for Erbb2-induced mammary tumorigenesis (31). …”
Section: Discussionmentioning
confidence: 92%
“…Moreover, increased Ras activation could also contribute to PI3K signaling. In a similar study, Erbb3-mediated PI3K signaling was shown to be dispensable for Erbb2-induced mammary tumorigenesis (31). …”
Section: Discussionmentioning
confidence: 92%
“…In the mouse, ErbB3 is required, via phosphoinositide 3-kinase signalling, for the development of the ducts during mammary gland development, but is not essential for the formation of lobules during pregnancy [51,52]. Balko and colleagues reported that ERBB3 expression in the mammary epithelium is highest in the luminal cell populations and lowest in the basal cells, and that loss of ErbB3 in the luminal cell compartment in mice results in an increase in apoptosis of these cells and an expansion of the basal cell population via paracrine signalling [53].…”
Section: Discussionmentioning
confidence: 99%
“…This gene is included in the group of genes that regulate breast cancer metastasis, as a metastasis suppressor [52]. Whereas no studies have reported an association of this gene with dairy related traits, there is a functional relationship between CD82 and ERBB3 (Receptor tyrosine-protein kinase erbB-3) [53], which is related to normal mammary development [54].…”
Section: Discussionmentioning
confidence: 99%